Implementation of the project-based learning (PjBL) model in sharpening students' critical thinking as an effort to strengthen the profile of Pancasila students - Alfi Nur Hidayati; Akhtim Wahyuni (Indonesian Institute for Counseling, Education and Therapy (IICET), 2023)
This study aims to determine the Critical Thinking of students by implementing a project-based learning model in science subjects. This research method uses Descriptive Qualitative method. By using the source triangulation technique to obtain and process data. This research was conducted at SDN Celep 1 Sidoarjo with the primary subject of class teachers and grade IV students, while the secondary subject of this research is the learning outcomes of students obtained from teachers and supporting data in the form of literature. Based on the results of research data analysis through interviews, observations, analysis of the process and student learning outcomes, it shows that learning using projects can improve students' Critical Thinking. In addition, students can find out how to make projects with high precision. Based on the researcher's observations, it can be concluded that each stage of implementing a project-based learning model can develop one of the dimensions of the Pancasila Learner Profile, namely Critical Thinking. So that learners get better information from their learning experience.